Constraints on the position and interpretation of bare singular indefinites in Russian - Borik, Olga (Linguistica (Ljubljana), 2016)
In this paper, I discuss the distribution of bare singular indefinite nominals in Russian. I argue that these nominal phrases are full-fledged indefinites and can have both specific and non-specific indefinite interpretations. However, their appearance in the preverbal subject position is not common. I argue in this paper that this restriction exists because a specific interpretation, or, in other words, a referential reading, required for this position cannot be unambiguously established with BSgs without any additional sentential specification. Additionally, I discuss some consequences of my proposal, such as BSg subjects of individual-level predicates, and BSg subjects in thetic judgments.
Keywords: forme indéfinie; nedoločna oblika; nom; russe; Russian; ruščina; samostalnik; semantics; semantika; sémantique; skladnja; syntax; syntaxe